Local Labor Markets and Welfare Spells: Do Demand Conditions Matter? - Hoynes, Hilary Williamson (The Review of Economics and Statistics, 2000)
This paper examines the impact of changes in labor market conditions on participation in the Aid to Families with Dependent Children (AFDC) program in California. Transitions off welfare and transitions back onto welfare are estimated using discrete duration models that control for local labor market conditions, demographic and neighborhood characteristics, duration effects, county-fixed effects, time effects, and county- specific time trends. The results show that higher unemployment rates, lower employment growth, lower employment-to-population ratios, and lower wage growth are associated with longer welfare spells and higher recidivism rates. Hispanics, blacks, and two-parent families are the groups that are most sensitive to changes in local labor market conditions.